2019
DOI: 10.1177/1535370219854678
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of WW domain-containing oxidoreductase leads to tamoxifen-resistance by the inactivation of Hippo signaling

Abstract: Acquired tamoxifen-resistance is an important cause of death in patients with hormone-dependent breast tumors. Therefore, understanding the molecular mechanisms underlying the development of tamoxifen-resistance is critical for successful endocrine therapy. This study aimed to define the role of WW domain-containing oxidoreductase (WWOX) in acquired tamoxifen-resistance. Our results show that low WWOX expression was significantly related to tamoxifen-resistance. Moreover, WWOX-knockdown increased resistance to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Supporting research from WWOX also shows this protein may oversee the Hippo signaling pathway from the upstream via interacting with proteins in the TGF-β, hyaluronidase Hyal-2, and Wnt/β-catenin pathways (Chen et al). In supporting this notion, a recent study reported that downregulation of WWOX results in tamoxifen resistance in breast cancer due to inactivation of Hippo signaling (3). Lee and Liou described the structure and the functional nature of Pin1.…”
mentioning
confidence: 87%
“…Supporting research from WWOX also shows this protein may oversee the Hippo signaling pathway from the upstream via interacting with proteins in the TGF-β, hyaluronidase Hyal-2, and Wnt/β-catenin pathways (Chen et al). In supporting this notion, a recent study reported that downregulation of WWOX results in tamoxifen resistance in breast cancer due to inactivation of Hippo signaling (3). Lee and Liou described the structure and the functional nature of Pin1.…”
mentioning
confidence: 87%
“…Simultaneous inhibition of YAP1 and ROR1 in combination with conventional HER‐2 therapy may overcome treatment resistance problem 203 . Evidence suggests that WW domain‐containing oxidoreductase inhibits YAP activity by increasing the phosphorylation of YAP in breast cance 204 . The antipsychotic drug chlorpromazine inhibits BC cell stemness, downregulates Hippo–YAP signaling, and increases BC cell resistance to drugs 244 .…”
Section: Hippo Pathway In Cancer Drug Resistancementioning
confidence: 99%
“… 203 Evidence suggests that WW domain‐containing oxidoreductase inhibits YAP activity by increasing the phosphorylation of YAP in breast cance. 204 The antipsychotic drug chlorpromazine inhibits BC cell stemness, downregulates Hippo–YAP signaling, and increases BC cell resistance to drugs. 244 Moreover, methotrexate‐free can make BC stem cell lines and related tumors more sensitive to the drug resistance of transplanted tumors.…”
Section: Hippo Pathway In Cancer Drug Resistancementioning
confidence: 99%
“…Moreover, Zheng et al [ 108 ] found that the YAP-glycolysis axis was also a target for overcoming tamoxifen resistance, based on the fact that the Hippo pathway was downstream of GPER. Li et al [ 109 ] confirmed that downregulated YAP phosphorylation and upregulated YAP nuclear translocation directly resulted in tamoxifen resistance, which was reversed by YAP silencing.
Fig.
…”
Section: The Cross Talk Between the Hippo Pathway And Multiple Pathways Involved In Endocrine Resistancementioning
confidence: 99%